Praktik Wirausaha Sejak Dini dalam Mengembangkan Kemampuan Sosial Anak: Sebuah Studi Kasus - Muhammad Abdul Latif; Ayu Rahmawati; Nihayatul Mahsudah (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aims to explore the implementation of early entrepreneurship practices and examine their contribution to the development of children’s social skills at TK Muslimat NU Darunnajah Kamal. The study is based on the premise that introducing entrepreneurship through authentic learning experiences can foster positive social behaviors from an early age. Methods – This study employed a qualitative case study design. Participants consisted of one school principal, teachers, and parents of children enrolled at TK Muslimat NU Darunnajah Kamal. Data were collected through semi-structured interviews, classroom observations, and document analysis. The data were analyzed using thematic analysis, including familiarization with the data, coding, theme development, and interpretation. Findings – The findings revealed that early entrepreneurship practices were implemented through activities such as cooking class and market day. These activities provided children with authentic opportunities to prepare products, present their work, engage in buying and selling, and interact with peers and adults. Participation in these activities contributed to children's social development by strengthening cooperation, role sharing, respect for others, communication skills, self-confidence, and responsibility during collaborative learning experiences.Research Implications – The findings suggest that early entrepreneurship practices can serve as an innovative pedagogical approach for promoting children's social development through authentic and experience-based learning.